Analysis of optical mineralogy of cement – enamel junction in deciduous dentition - Arunachalam, Preethi (J Oral Maxillofac Pathol, 2019)
BACKGROUND: Optical analysis of mineralized tissues with polarized microscopy is based on the mechanism of light interaction with biological tissues and spatial distribution of light. Understanding the light propagation mechanisms in mineralized tissues has huge clinical relevance in terms of esthetics and restoration. The present study aims to analyze the mineralogy characteristics of the cementoenamel junction (CEJ), which is a vital region involving merger of tissues with varied embryological origins. AIM: To analyze the mineralogy characteristics and CEJ patterns in deciduous teeth. OBJECTIVES: The variations of CEJ pattern in deciduous teeth and mineralogy characteristics such as retardation and birefringence are compared to the adjacent regions of underlying dentin corresponding to the permanent dentition. RESULTS: Mineralogy characteristics showed variation near the CEJ when compared to the adjacent regions of underlying dentin (statistically significant [P < 0.05]). When compared to permanent dentition, they showed a numerical difference, but the values were statistically insignificant. CEJ pattern analysis predominantly showed edge-to-edge interrelation, followed by root cementum overlapping the enamel and gap type. CONCLUSION: Analyzing CEJ in primary dentition is of paramount importance as it is a vulnerable zone in terms of caries progression and restorative margins. Increased edge-to-edge type of CEJ suggests a natural shield-like protection offered by enamel. Variations in mineralogy characteristics in the CEJ of deciduous dentition suggest the increased mineral content than in the adjacent regions of underling dentin. However, further investigations using advanced techniques for mineralogy analyses such as atomic force microscopy can help yield more intricacies of hard tissues of tooth.